If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(2x+3)-(4x-1)=19
We move all terms to the left:
-2(2x+3)-(4x-1)-(19)=0
We multiply parentheses
-4x-(4x-1)-6-19=0
We get rid of parentheses
-4x-4x+1-6-19=0
We add all the numbers together, and all the variables
-8x-24=0
We move all terms containing x to the left, all other terms to the right
-8x=24
x=24/-8
x=-3
| 36^{3x}=216^{2x+1} | | (3n-18)=2n-4(-2n) | | 2y-10y=0 | | 63s^2+32s-63=0 | | 45x+11=45x+49 | | 55−(2c+3)=4(c+6)+c | | -2(r+9)=33 | | –11x−–10x=9 | | 2x+4(-x+3)-4=0 | | 11x+39=−16 | | 180=50+(y+10)+2y | | -5.6(x-2.75)=11.2 | | X2º+b2º=30 | | z-3/16=7/16 | | -(x-1)+2(3-x)=-2 | | 15c+85=c | | {11(y-10)}=(4y-5 | | 10-4×=3y | | 2/3=2x-7/3x+4 | | (x+19)=(5x-45) | | -6k=6-6k | | 180=(y+10)+2y | | 3m−2m=5 | | –10−2h=–3h | | 6(3x+1)=-102 | | 58=8+5n | | 13x+4=27x-2 | | 8-2(4x-3)=-26 | | 2(x+2)-2=4x-2(-3+x) | | 3.2=-0.4nn= | | 5(w+7)=-5(3w-4)+2w | | 3+6b=2b+3b |